Enablers and barriers for adoption of lean system: a mix method approach. (28th February 2022) - Zia-ur-Rehman, Muhammad; Hashim, Muhammad; ,; Iqbal, Shahzad; Baig, Sajjad Ahmad; Khalid, Yusra; Khan, Ayesha
This study is based on exploring the lean manufacturing practices in Pakistan's textile industries. This study adopts the triangulation method for deciding barriers to lean's implementation in Pakistan's textile sector. We used descriptive analysis for the interpretation of the data for quantitative analysis. We conducted root causes analysis through expert interviews and also identified enablers of lean implementation in Pakistan's textile industry using qualitative and quantitative analysis. After the interview, we learned that poor leadership, insufficient preparation, unavailability of local experts, confusion, and poor communication are crucial barriers to lean implantation. We have also identified drivers of successful lean implementation in lean. 5S is the most used tool in the local textile organisation. This paper examines the current situation of lean implementation in Pakistan. This paper highlights the leading causes in poor implementation of lean that can be addressed through the study's solution. This study could be a source of inspiration for small and medium-sized enterprises to apply lean in their organisation.